2019
DOI: 10.1097/iae.0000000000002110
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Early Anatomic Response to Anti–vascular Endothelial Growth Factor Therapy and Long-Term Outcome in Diabetic Macular Edema

Abstract: Early CRT response to ranibizumab is a significant prognostic indicator of medium- to long-term anatomical outcome in center-involved diabetic macular edema.This is an open-access article distributed under the terms of the Creative Commons Attribution-Non Commercial-No Derivatives License 4.0 (CCBY-NC-ND), where it is permissible to download and share the work provided it is properly cited. The work cannot be changed in any way or used commercially without permission from the journal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
50
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(59 citation statements)
references
References 51 publications
5
50
0
4
Order By: Relevance
“…A unique feature of the current analysis is that anatomic response to ranibizumab was assessed longitudinally over the first 52 weeks of treatment rather than at a single time point. This is in contrast to previous Early Anti-VEGF Response and Long-term Efficacy programme analyses, which typically assessed anatomic response to ranibizumab at week 12 of treatment (i.e., after the first three monthly intravitreal injections) and failed to demonstrate a significant association between early CRT reduction and longterm BCVA improvement [31]. Similarly, retrospective analyses of the RISE/RIDE study data suggest a dissociation between early anatomic response to ranibizumab after the third monthly intravitreal injection and long-term (2-year) visual acuity outcome in DMO [29].…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…A unique feature of the current analysis is that anatomic response to ranibizumab was assessed longitudinally over the first 52 weeks of treatment rather than at a single time point. This is in contrast to previous Early Anti-VEGF Response and Long-term Efficacy programme analyses, which typically assessed anatomic response to ranibizumab at week 12 of treatment (i.e., after the first three monthly intravitreal injections) and failed to demonstrate a significant association between early CRT reduction and longterm BCVA improvement [31]. Similarly, retrospective analyses of the RISE/RIDE study data suggest a dissociation between early anatomic response to ranibizumab after the third monthly intravitreal injection and long-term (2-year) visual acuity outcome in DMO [29].…”
Section: Discussionmentioning
confidence: 68%
“…The Early Anti-VEGF Response and Long-term Efficacy programme, a series of post hoc analyses of data from the Diabetic Retinopathy Clinical Research Network's Protocol I trial [5], one of the largest published studies of ranibizumab in DMO, was initiated to explore the relationship between early and long-term anti-VEGF treatment outcomes. Analyses to date have demonstrated a significant association between early (12-week) and long-term (1-to 3-year) BCVA improvement with ranibizumab [30], but an apparent dissociation between early reduction in macular thickness and long-term BCVA improvement [31]. Given that the use of anti-VEGF treatment in clinical practice is based in large part on optical coherence tomography changes, the present analysis explores the anatomic-functional relationship further by assessing macular thickness over the course of ranibizumab treatment rather than at a single time point.…”
Section: Introductionmentioning
confidence: 99%
“…111 In DME patients, post hoc analysis of data from Protocol I of the DRCR Network demonstrated that the initial macular response to three injections of a particular anti-VEGF agent was predictive of long-term outcome. 112 Accordingly, poor responders might potentially benefit from a switch in therapeutic agents.…”
Section: Anti-vegf Therapymentioning
confidence: 99%
“…Eine Gruppe von Autoren argumentiert auf Basis der funktionellen oder morphologischen Veränderungen bis Monat 3, dass diese schon zu diesem Zeitpunkt eine Empfehlung im Hinblick auf einen Medikamentenwechsel zulassen könnten [269,270]. Andere Autoren weisen darauf hin, dass gerade solche Patienten trotz des oben erwähnten geringen Visusgewinns bis Monat 3 ("suboptimal response") doch nach 2 Jahren bei konsequenter Fortsetzung des Anti-VEGF-Therapieschemas noch eine relative Visusbesserung oder das Erreichen eines absoluten Visusniveaus (≥ 0,5) zeigten [271].…”
Section: Wiederbehandlungsstrategie Bei Ivom Mit Vegf-inhibitorenunclassified